Complex morphotropic phase transformations and high piezoelectric properties in new ternary perovskite single crystals. (1st May 2018) - Liu, Zenghui; Wu, Hua; Ren, Wei; Ye, Zuo-Guang
Abstract: In order to understand the complex phase symmetry and phase transitions, and to illustrate the microscopic mechanisms of high piezoelectricity, single crystals of a new ternary complex perovskite system, Pb(Mg1/3 Nb2/3 )O3 -Bi(Zn2/3 Nb1/3 )O3 -PbTiO3, are grown by the high temperature solution growth method and their domain structure, dielectric and ferro-/piezoelectric properties, and phase transformation behavior are investigated by various techniques. Different phase symmetries including the rhombohedral, tetragonal and monoclinic are found in these crystals, indicating that the composition of the crystals is close to the morphotropic phase boundary (MPB) region. Most interestingly, unusual phase transformation sequences of rhombohedral → monoclinic → cubic, and monoclinic → cubic are directly observed by polarized light microscopy and confirmed by the dielectric and birefringence results. Moreover, an ultrahigh piezoelectric coefficient d 33 ≈ 2000 pC/N is obtained in these crystals, making these crystals useful for applications as electromechanical transducers. The unusual phase transformation sequences and the high piezoelectric response are explained from the polarization rotation mechanism, which has been evidenced in this work. Based on these results, a temperature-composition phase diagram is established, which illustrates the complex phases present and their transformation behavior. These studies provide new insights into the intricate morphotropic phase symmetry and phase components in complex perovskite solid solutions, and a better understanding of the microscopic mechanisms of high piezoelectric response in relaxor-based piezocrystals, which in turn will be helpful for designing better piezoelectric single crystals. Graphical abstract: Image 1